House of Representatives: democracy and equal opportunities between women and men? (Cadernos de Psicologia Social do Trabalho, 2012)
This research analyzed women's opportunities in terms of equality in the occupation of high leadership positions in the Brazilian House of Representatives. The field research was carried out from November 2005 to January 2006 and the survey comprised 1,320 respondents. The Perception Scale of Equal Opportunities Between Women and Men was applied to analyze the attitude of public servants with regard to women's ascension possibilities and limitations within the position structure of the organization. The scale consisted of 34 items, with Likert-style responses, and 6 items on demographic data. Data collection was carried out using the internal computer network of the House of Representatives, through an e-mail sent to the 3,597 effective public servants. Data underwent principal component analysis (PCA), promax rotation, with meritorious results (KMO = 86.0; Bartlett:14894.879), to 4 factors. Differences between men and women were observed with regard to the scores obtained. The opportunities of occupying a high leadership position are smaller for women than men. There are more male managers, and the public servants, especially women who don't occupy chief positions, notice that there're no equal opportunities between employees of both sexes.